The myocardium - Langer, Glenn A., 1928-2019 (Academic Press, 1997)
The Myocardium, Second Edition is a comprehensive presentation of cardiac function, including ultrastructure, cellular development and morphogenesis, ion channels, ion transporters, excitation-contraction coupling and calcium compartmentation, mechanics and force production, and energy metabolism. The Second Edition presents the new molecular, subcellular, and cellular developments which have occurred in this rapidly expanding field during the past 22 years. Key Features * Comprehensive overview of all aspects of heart function at the cellular, subcellular, and molecular level * Integrates molecular events to give understanding of global cardiac function * Includes basis of important pathological states.